Comparison of facilities management in private domestic buildings among different elderly groups in Hong Kong. Issue 7 (8th May 2018) - Leung, Mei-yung; Famakin, Ibukun Oluwadara; Ahmed, Khursheed
Abstract : Purpose: Personal characteristics, such as age, marital status, education level and gender, vary among elderly residents in residential apartments. These characteristics may influence the elderly residents' satisfaction with the facilities provided in their residential apartments. To ensure appropriate facilities management (FM) items are provided for the different categories of elderly people, it is necessary to understand their basic needs. Therefore, this paper aims to compare the satisfaction with FM items among elderly people with different personal characteristics in private domestic (PD) buildings. Design/methodology/approach: A questionnaire survey was conducted among elderly people with different personal characteristics in PD buildings to collect information about their levels of satisfaction with FM items. A total of 41 FM items and four characteristics of the elderly, namely, age, gender, marital status and education, were identified in this study. Findings: The result shows that satisfaction with natural daylight was significantly different among elderly people of different genders, while the one-way between-groups ANOVA indicate that satisfaction with the size of bedrooms, turning spaces at doors, temperature in bathrooms and/or toilets, colour, accessibility and ease of closing or opening the doors were significantly different among elderly people belonging to different age groups and of different marital status and education level. Originality/value: Designers and private developers are therefore recommended to increase the sizes of bedrooms, install windows on opposite sides of walls in the flats and ensure there is an adequate light reflection ratio for wall and floor colours, to accommodate elderly people's special characteristics.